The Kawarbaghi Incident and its Impact on Iraqi Politics (June-November 1946) (Journal of the College of Basic Education, 2025)
The Kawarbaghi ​​Incident is the first bloody clash between the authorities and the workers. This incident left its impact on the nature of union work in Iraq. The authorities wanted to give a lesson to the workers to reject strikes and stay away from union work, but the result was completely the opposite; the workers' awareness intensified and their support for their unions increased, and the struggle for the union became the focus of the working class's struggle later After the end of World War II, an important shift occurred in the history of contemporary Iraq, through the development of concepts of political work and the increase in national awareness demanding democratic freedoms and the establishment of political parties as the cornerstone for building democratic life in the countries of the liberated world, including Iraq. Therefore, the labor movement emerged as a political and professional force that contributed to political events.